THE INFLUENCE OF AGRIBUSINESS SUBSYSTEM ON BEEF CATTLE FATTENING FARM’S PROFIT IN CENTRAL JAVA - Prasetyo, E.; Sunarso, S.; Santosa, P.B.; Rianto, E. (Diponegoro University, 2012)
This study was aimed : (i) to know the subsystem implementation and agribusiness planning inbeef cattle fattening; (ii) to count the profit of beef cattle farming; (iii) to analyze the effect ofagribusiness subsystem implementation and agribusiness planning to beef cattle fattening profit. Thisstudy was carried out using survey method and the elementary units were feedlot farmers. The samplewas determined by Purposive Quota Sampling Method on 112 respondents spread across five regencies,namely Blora, Rembang, Grobogan, Wonogiri, and Boyolali. Data were collected from primary andsecondary sources. The data analysis used quantitative descriptive and inferential statistics method,which include scoring, financial, and multiple linear regression analysis. The results showed that : (i) theimplementation of agribusiness subsystem (including preproduction subsystem, marketing, andagribusiness support services) and agribusiness planning were not so good category, while the cattlefarming subsystem was moderate category; (ii) the average of farming scale in each feedlot farmer was2.95 head of cattle with the profit rate was IDR 1,044,719 per fattening period during 6.68 months(equivalent to IDR 156,395 per month); (iii) agribusiness subsystem and agribusiness planning hadsignificant impact on feedlot farmer profit simultaneously, but preproduction subsystem and theagribusiness support services subsystem partially had a significant impact on feedlot farmer profit.